Intergametophytic selfing and microgeographic genetic structure shape populations of the intertidal red seaweed Chondrus crispus. Issue 12 (7th January 2013) - Krueger‐Hadfield, S. A.; Roze, D.; Mauger, S.; Valero, M.
Abstract Understanding how abiotic factors influence the spatial distribution of genetic variation provides insight into microevolutionary processes. The intertidal seascape is characterized by highly heterogeneous habitats which probably influence the partitioning of genetic variation at very small scales. The effects of tidal height on genetic variation in both the haploid (gametophytes) and diploid (tetrasporophytes) stages of the red alga Chondrus crispus were studied. Fronds were sampled every 25 cm within a 5 m × 5 m grid and along a 90‐m transect at two shore heights (high and low) in one intertidal site in France. The multilocus genotype of 799 fronds was determined (Nhaploid = 586; Ndiploid = 213) using eight microsatellite loci to test the following hypotheses: (i) high and low shore fronds belong to genetically differentiated populations, (ii) gene flow is restricted within the high shore habitat due to tidal‐influenced isolation and (iii) significant FIS values are driven by life history characteristics. Pairwise FST estimates between high and low shore levels supported the hypothesis that high and low shore fronds were genetically differentiated. The high shore was characterized by the occurrence of within‐shore genetic differentiation, reduced genetic diversity and increased levels of intergametophytic selfing, suggesting it is a marginal environment. These results suggest at fine scales within the intertidal seascape the same mechanisms as those over the species' distributional range are at work with core and marginal population dynamics.